On the Rationality of Worldview Beliefs According to Ryszard Kleszcz - Łukasiewicz, Dariusz (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The paper discusses Ryszard Kleszcz’s epistemological views, with the focus on his conception of rationality of beliefs. It aims to show that Kleszcz has adopted many of the ideas of logical rationalism typical of the Lvov-Warsaw School, but these ideas have been developed and significantly modified in his works. Kleszcz argues that the binary division of beliefs into rational and irrational is difficult to defend, and it is more justified and practicable to hold that belief’s rationality is gradable; thus, metaphysical and religious beliefs could be – to a certain degree – rational as well.